Perbandingan Sifat Kimia dan Biologi Tanah Akibat Keterbukaan Lahan Pada Hutan Reboisasi Pinus di Kecamatan Pollung Kabupaten Humbang Hasundutan Sumatera Utara - Basuki Wasis; Yadi Setiadi; Mohamad Eko Purwanto (Jurnal Silvikultur Tropika, 2012)
Comparison of Soil’s Chemical and Biological Characteristics Caused Land Openness of Pine Reforested Forest in Pollung Sub-district of Humbang Hasundutan District, North Sumatera.Forest clearing activity has been caused land openness in some forest areas such as reforested forest. Land openness could cause the decreasing of fertility value of forest soil. The objective of this research was to comparing of soil’s chemical and biological characteristics in open area with pine forest in pine reforested forest in Pollung sub-district of Humbang Hasundutan district, North Sumatera. This research was using secondary data of soil’s chemical and biological characteristics analysis results from Team of Living Environmental Ministry 2010. Descriptively, this research has shown that land openness has caused lower comparison of all average value of soil’s chemical and biological parameters. Highest percentage of comparison difference in open area was total of C-organic content that amounted 59.90% and total of soil fungi that amounted 94.18 % lower than pine forests. Degradation of soil’s chemical and biological values was caused by the decreasing of total organic content of soil and nutrient washing by rain water. Considering to negative impact that will be caused thus needed an effort of soil resiliency through land rehabilitation by whitewashing of acid soil and re-vegetation